TIMELINESS OF FINANCIAL REPORTING AND INVESTMENT DECISION DYNAMICS: EVIDENCE FROM QUOTED DEPOSIT MONEY BANKS IN NIGERIA - Ehigie Ikponmwosa Darlington; Jackson-Akhigbe Beauty E (PhD); Abusomwan Rachael E. (PhD) (Gusau Journal of Accounting and Finance)
Thisstudyexaminedtherelationship between the timeliness offinancialreporting andinvestmentdecisionsofquoteddepositmoney banks in Nigeria.Ex-post facto research design was employed and the sample population is made up of 12 depositmoney banks quoted companies in the Nigerian Stock Exchange (NSE). The depositmoney banks for the population must have the responsibility to publish its financial statements for the period from 2012 to 2023. The data are analyzed using descriptive statistics, Pearson correlation and ordinary least square (OLS) regression technique.The result shows that the timeliness of financial reporting has a negative and statistically significant relationship with investment decision dynamics of money deposit banks in Nigeria and financial reporting quality has positive and statistically significant relationship with investment decision dynamics of money deposit banks in Nigeria at 5% level.The study recommended that stakeholders of depositmoney banks in Nigeria should set a time limit for the managing director to present the financial report and accounts for the external auditors to report timely, since timeliness of financial reporting has an adverse effect on investment decision dynamics.